2015
DOI: 10.5194/acp-15-11081-2015
|View full text |Cite
|
Sign up to set email alerts
|

VOC species and emission inventory from vehicles and their SOA formation potentials estimation in Shanghai, China

Abstract: Abstract. Volatile organic compound (VOC) species from vehicle exhausts and gas evaporation were investigated by chassis dynamometer and on-road measurements of nine gasoline vehicles, seven diesel vehicles, five motorcycles, and four gas evaporation samples. The secondary organic aerosol (SOA) mass yields of gasoline, diesel, motorcycle exhausts, and gas evaporation were estimated based on the mixing ratio of measured C2–C12 VOC species and inferred carbon number distributions. High aromatic contents were mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 54 publications
4
35
1
1
Order By: Relevance
“…Among aromatics, benzene and toluene contributed approximately 9 % to the total VOC emissions. This result was consistent with a study by Huang et al (2015) on diesel emissions in Shanghai. In view of oxygenated VOCs and haloalkane contents, acetone and CH 2 Cl 2 exceeded benzene and toluene.…”
Section: Voc Speciationsupporting
confidence: 93%
See 3 more Smart Citations
“…Among aromatics, benzene and toluene contributed approximately 9 % to the total VOC emissions. This result was consistent with a study by Huang et al (2015) on diesel emissions in Shanghai. In view of oxygenated VOCs and haloalkane contents, acetone and CH 2 Cl 2 exceeded benzene and toluene.…”
Section: Voc Speciationsupporting
confidence: 93%
“…It was observed that the relative signal area of EC ions was higher and more widely distributed than for OC Figure 3. Comparison of SOA yields and OFP based on VOC source profiles with calculated results from previous studies Cao et al, 2015;Huang et al, 2015). The purple dots represent ships tested in this study.…”
Section: Average Ion Mass Spectramentioning
confidence: 74%
See 2 more Smart Citations
“…This provides confidence that 891 the calculation described in SI 6 captures the chemical production of SOA over Seoul. Also, the 892 difference between the estimated and measured OA is comparable to, or better than, found in other 893 studies that utilized a similar modeling approaches (Dzepina et al, 2009;Zhao et al, 2014Zhao et al, , 2016894 Hayes et al, 2015;Huang et al, 2015;Ma et al, 2017), and within the uncertainty of the measured 895 OA (38%, 2σ). 896…”
Section: Calculated Precursor Contributions To the Soa Production Ovementioning
confidence: 55%